"It gives you that sense of hope": An exploration of technology use to mediate student engagement with mathematics. Issue 1 (January 2020) - Attard, Catherine; Holmes, Kathryn
Abstract: Despite the predicted need for a more mathematically capable workforce, the proportion of students undertaking advanced mathematics courses in Australia and other comparable countries has stagnated or fallen, in part due to a lack of student engagement with mathematics in school. In society in general, technology use is commonplace, leading some educators to speculate that technology use for the teaching and learning of mathematics can improve student engagement. In this paper, using multiple case studies, we examine how teachers (n = 10), recognised by their peers as exemplary users of technology, take advantage of technological affordances to optimise student engagement with mathematics. Data was collected from three participant groups: Teachers, Leaders (n = 10), and student focus groups (n = 6). We examine both student and teacher perspectives, through the lens of the Framework for Engagement with Mathematics (FEM), to tease out the ways in which exemplary teachers use technology to enhance pedagogical relationships with students and their pedagogical repertoires. We find that the teachers and students reported evidence of all elements of the FEM, but to differing degrees. In particular, we identified that teachers used technological tools to enhance teacher awareness of individual student learning needs and to promote student-centred pedagogies leading to greater student engagement with mathematics. We contend that a greater awareness of the nuanced pedagogical affordances of a range of technological tools could lead teachers toward practices that enhance student engagement with mathematics, leading to an increase in students wishing to extend their mathematical knowledge beyond the compulsory school years. Abstract : Education; Secondary classrooms; Mathematics education; Student engagement; Educational technology; Primary classrooms; Technology and mathematics.